HUBUNGAN EMPIRIS INTENSITAS SEISMIK DENGAN PARAMETER GETARAN TANAH DI WILAYAH JAWA BARAT - Kadnan, Kadnan (Jurnal Widya Climago, 2019)
West Java is a seismically active region with the largest population in the Indonesia region. The seismicity of West Java region due to the subduction of the Indo-Australian plate to the Eurasian plate-fault and local fault activity on the mainland. The more dense residential population even in seismic areas, damageand loss estimation of seismic hazard increasingly necessary in order mitigation and emergency response. Macroseismic study in West Java is also very important in revising the history of seismicity in the past and needed in the investigation of the potential seismic hazard. The regression approach has been carried out to determine the seismic intensity attenuation models and empirical relationships of seismic intensity with Peak Ground Velocity (PGV) and Peak Ground Acceleration (PGA) in West Java by using the Broadband signal recorded on the Libra-station network BMKG for earthquakes with M> 4 that occurred in the period 2009 to 2011. The differentiation techniques applied to the velocity seismogram to get the acceleration seismogram. From the calculations, obtained the empirical relationships seismic intensity with PGV and PGA as follows: IMM = 3,56 log(PGV) + 2,88 ± 0,57 (V≤ IMM ≤VIII)IMM = 3,69 log(PGA) – 1,12 ± 0,51 (V ≤IMM ≤VIII) The combination of seismic intensity attenuation models and empirical relationships of IMM – PGV andIMM – PGA are useful for prediction and fast estimation of the potential for earthquake damage and the intensity mapping (ShakeMap) in order to Earthquake Early Warning.